2019
DOI: 10.24095/hpcdp.39.10.01
|View full text |Cite
|
Sign up to set email alerts
|

Evidence synthesis - Neighbourhood retail food outlet access, diet and body mass index in Canada: a systematic review

Abstract: Introduction There is growing interest in the role of food environments in suboptimal diet and overweight and obesity. This review assesses the evidence for the link between the retail food environment, diet quality and body mass index (BMI) in the Canadian population. Methods We conducted a systematic keyword search in two bibliometric databases. We tabulated proportions of conclusive associations for each outcome and exposure of interest. Absolute and relative measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 39 publications
2
26
0
Order By: Relevance
“…Fourteen reviews 26,27,32,[34][35][36][37][38][39][40][41][42][43][44] examined the association of the built environment (e.g., location/presence of food stores and fast-food restaurants) on dietary intake. Across reviews, outcomes focused primarily on fruit and vegetable intake and whether individuals met nutritional guidelines (e.g., recommendations for daily fruit and vegetable or fat consumption).…”
Section: Built Environment and Dietary Intakementioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen reviews 26,27,32,[34][35][36][37][38][39][40][41][42][43][44] examined the association of the built environment (e.g., location/presence of food stores and fast-food restaurants) on dietary intake. Across reviews, outcomes focused primarily on fruit and vegetable intake and whether individuals met nutritional guidelines (e.g., recommendations for daily fruit and vegetable or fat consumption).…”
Section: Built Environment and Dietary Intakementioning
confidence: 99%
“…Five reviews 27,34,36,37,43 reported support for associations between greater access to supermarkets and higher diet quality (e.g., higher intake of fruits and vegetables, lower intake of saturated fats, or higher overall diet quality index scores) whereas five others (including two reviews focused on natural experiments) 26,27,38,39,41 reported primarily null results. Three reviews 35,37,41 reported significant associations between access to fast-food restaurants and lower diet quality, whereas five others 38,39,[42][43][44] reported primarily null results. In a review of natural experiments, Woodruff and colleagues 32 reported that the opening of a new food retailer (e.g., a supermarket, farmers market, or produce stand) tended to produce some short-term increases in fruit and vegetable consumption in adults who choose to shop at these establishments; however, there was little evidence supporting the longer-term persistence of these effects or of broader community impacts on fruit and vegetable consumption.…”
Section: Built Environment and Dietary Intakementioning
confidence: 99%
“…As the groups for ethnicity (non-Whites) were not specific, we did not include ethnicity as a covariate. The original study from which these data were collected investigated relations between the built environment and physical activity (McCormack et al, 2012), thus other built characteristics not available in these data but associated with weight (e.g., food destinations (Stevenson, Brazeau, Dasgupta, & Ross, 2019)) were not included. Our study included mostly established or "built-out" Calgary neighbourhoods that existed in 2007 and 2008.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…For instance, neighbourhoods with highly connected streets, high population density and a variety of destinations are associated with higher levels of physical activity and less sedentary behaviour [45] and obesity [45,46]. Tobacco and alcohol outlet density are associated with smoking and alcohol consumption behaviours [47,48], and there is mixed evidence that access to healthy/unhealthy food retail locations is linked to diet and obesity [49][50][51]. Greener neighbourhoods with more parks and vegetation are also linked to higher levels of physical activity [52,53] mental health and wellbeing [52,54], and lower levels of stress [52] and obesity [53].…”
Section: Introduction 1rationalementioning
confidence: 99%